2018
DOI: 10.12688/f1000research.17187.1
|View full text |Cite
|
Sign up to set email alerts
|

A bovine CD18 signal peptide variant with increased binding activity to Mannheimia hemolytica leukotoxin

Abstract: Background: Mannheimia haemolytica is the major bacterial infectious agent of bovine respiratory disease complex and causes severe morbidity and mortality during lung infections. M. haemolytica secretes a protein leukotoxin (Lkt) that binds to the CD18 receptor on leukocytes, initiates lysis, induces inflammation, and causes acute fibrinous bronchopneumonia. Lkt binds the 22-amino acid CD18 signal peptide domain, which remains uncleaved in ruminant species. Our aim was to identify missense variation in the bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We investigated whether Bov-A2 elements are a source of modern variation by using MELT (Gardner et al 2017) to identify polymorphic mobile element insertions in a diverse panel of 38 cattle whole-genome sequences (Workman et al 2018;Tsuda et al 2013;Stothard et al 2015;Shin et al 2014;Bickhart et al 2016;Heaton et al 2016;Chen et al 2018). Across all individuals, our analysis revealed 1017 Bov-A2 elements with read-supported evidence for insertional polymorphism, including 740 non-reference insertions and 277 deletions relative to the reference Hereford bosTau9/ARS-UCD1.2 assembly (Fig.…”
Section: Tes Contribute To Evolutionary Diversification Of Ruminant Immune Responsesmentioning
confidence: 99%
“…We investigated whether Bov-A2 elements are a source of modern variation by using MELT (Gardner et al 2017) to identify polymorphic mobile element insertions in a diverse panel of 38 cattle whole-genome sequences (Workman et al 2018;Tsuda et al 2013;Stothard et al 2015;Shin et al 2014;Bickhart et al 2016;Heaton et al 2016;Chen et al 2018). Across all individuals, our analysis revealed 1017 Bov-A2 elements with read-supported evidence for insertional polymorphism, including 740 non-reference insertions and 277 deletions relative to the reference Hereford bosTau9/ARS-UCD1.2 assembly (Fig.…”
Section: Tes Contribute To Evolutionary Diversification Of Ruminant Immune Responsesmentioning
confidence: 99%
“…We investigated whether Bov-A2 elements are a source of modern variation by using MELT ( Gardner et al 2017 ) to identify polymorphic mobile element insertions in a diverse panel of 38 cattle whole-genome sequences ( Tsuda et al 2013 ; Shin et al 2014 ; Stothard et al 2015 ; Bickhart et al 2016 ; Heaton et al 2016 ; Chen et al 2018 ; Workman et al 2018 ). Across all individuals, our analysis revealed 1017 Bov-A2 elements with read-supported evidence for insertional polymorphism, including 740 nonreference insertions and 277 deletions relative to the reference Hereford bosTau9/ARS-UCD1.2 assembly ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study analyzing missense variants in the integrin β 2 gene (ITGB2) encoding CD18 of more than 1200 cattle from 50 different breeds revealed that missense variants in the CD18 signal peptide affect LktA binding. Consequently, animals carrying certain alleles can be more susceptible to the effects of LktA, and hence more prone to mannheimiosis [57]. These findings could be important to cattle breeding since M. haemolytica is spread widely in cattle herds.…”
Section: Lkta Leukotoxin Of Mannheimia (Pasteurella) Haemolyticamentioning
confidence: 99%